Workforce woman empowerment: Transforming challenges into opportunities in Karma Royal Bali as a timeshare hotel - Priliani, Ni Luh Dita; Kartini, Luh Putu; Adyatma, Prastha; Pitanatri, Putu Diah Sastri; Pitanatri, Made Uttari (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
This study identifies strategies to enhance women's empowerment in the workplace at Karma Royal Bali and examines how these efforts contribute to guest satisfaction within the timeshare hotel system. The research focuses on three properties: Karma Royal Candidasa, Karma Royal Jimbaran, and Karma Royal Sanur. This study used a qualitative methodology through in-depth interviews with women leaders and workers; the study explores themes of gender bias, work-life balance, and career development barriers. Findings highlight effective techniques these women implement to overcome challenges, including training programs, mentorship, and supportive workplace policies, ensuring high service quality and improving guest experiences. Therefore, this study implies that women's empowerment is vital in providing guest satisfaction.